Towards project-based science learning : a Finnish class teacher’s conceptions and implementation - Reddy, Shruthi Venkatesh (2020)
Previous implementation research on Project-based science learning (PBSL) has mostly focussed on teachers that were provided with training or in-practice support for the implementation of PBSL. Although teacher-initiated PBSL is the most common way students are introduced to projects, little is known about the quantity and quality of project implementation in the context of teacher-initiated PBSL. This in-depth case study of one Finnish elementary class teacher’s conceptions and implementation of PBSL seeks to understand how the teacher’s conceptions of PBSL relates to the implementation and how the teacher’s conceptions develop as a result of practical experience of implementing projects.